Differences Regarding Knowledge of Sexually Transmitted Infections, Sexual Habits, and Behavior Between University Students of Medical and Nonmedical Professions in Serbia - Slobodan Subotic; Vladimir Vukomanovic; Svetlana Djukic; Svetlana Radevic; Snezana Radovanovic; Danijela Radulovic; Katarina Boricic; Jelena Andjelkovic; Jelena Tosic Pajic; Ivana Simic Vukomanovic (Frontiers Media S.A., 2022)
Aim: The aim of this study is to assess the knowledge of sexually transmitted infections (STIs), sexual habits, and behavior among students of medical and nonmedical students in Serbia.Methodology: The cross-sectional study of 1,273 university students of four undergraduate institutions in Serbia, two of medical and two of nonmedical orientation. A standardized questionnaire, prepared in line with the questionnaire of the European health research-the second wave (European Health Interview Survey-EHIS wave 2), according to defined internationally accepted indicators, was used as a survey instrument.Results: Statistically significant difference (p < 0.001) between medical and nonmedical student groups was determined for the following parameters: naming four of five STIs (29.1 vs. 13.4%), knowledge about vaccines against some STIs (26.0 vs. 17.0%), relationship between HPV infection and cervical malignancy (48.2 vs. 16.7%) engaged in the sexual relations (87.9 vs. 76.4%), never used a condom (15.2 vs. 10.4%), underwent gynecological or urological examination (66.7 vs. 44.1%), and tested to one of STIs (10.5 vs. 4.9%).Conclusion: Both student groups have limited knowledge on possible consequences that risky sexual behavior has for reproductive health. Promotion of knowledge about STIs, awareness of all complications, and consequences of these infections certainly affect the reduction of risky behavior.